Application of Homogenized Load-Bearing Ring Hypothesis in Roadway Supporting - Quntao Zhang; Jianwei Zheng; Xiaodong Sun; Wenzhou Li; Kang Yi; Yukai Fu; Jiulin Shi; Shuai Wang; Biao Liu; Qi Wang (Shock and Vibration)
Artificial support system takes advantages of self-bearing capacity of surrounding rock mass in roadway support, which is one of the important supporting ideas in modern times. The implementation way of an artificial support system is worthy of deep investigation. In this study, an HLBR hypothesis was proposed with comprehensive consideration of mechanical properties of surrounding rock mass based on the reinforced arch theory and axial variation theory. A model of bearing structure in surrounding rock mass was constructed, and the stress state on the bearing structure was analyzed. It was believed that when the axial ratio (k) of this bearing structure is equal to the lateral stress factor (λ) (which is the optimal axial ratio), the tangential stress on the bearing boundary reaches the minimum and is in uniform distribution. At this moment, the roadway and the supporting structure can make good use of the self-carrying capacity of surrounding rock mass, which is conducive to lowering the stress distribution level of surrounding rock mass. According to prestress diffusion characteristics of bolt, some ways to achieve HLBR were proposed, which were the optimal axial ratio design, difference support and local grouting modification, and finally performance of the original support design in a belt roadway of the mining district IV of a mine in Shanxi Province. A new supporting scheme was provided according to the HLBR hypothesis. In addition, the FLAC3D strain-softening model was modified by C++, which was used to interpret the reasonability of the suggested supporting scheme. The proposed HLBR hypothesis discloses ways to use self-capacity of surrounding rock mass. This study provides a new idea for roadway sectional design and roadway support design, which are beneficial to maintaining the stability of surrounding rock mass in roadways.